Numerical and Analytical Determination of the Critical Wind Speed Causing the Overturning of the Top-Slewing Tower Crane - Marcin Augustyn; Marek Barski (Applied Sciences)
The current study is devoted to the problem of the stability of the top-slewing tower cranes concerning the wind. A sufficiently strong wind can cause the overturning of the whole crane. The critical wind speed varies significantly depending on the geometrical configuration of the crane with respect to the wind direction. At the very beginning, the aerodynamic forces are estimated using CFD simulations. Next, the obtained results are compared with the applicable standards. The critical wind speeds and corresponding jib rotation angles are determined for the following two selected crane configuration variants: crane without payload and crane with maximal payload located at the end of the jib. It occurred that the critical wind speed varies between 35 m/s and 53 m/s depending on the assumed variant. Moreover, the trace of the gravity center is also determined to validate the obtained results.